A 3D numerical model for the optimization of running tracks performance - Andena, L.; Aleo, S.; Caimmi, F.; Mariani, S.; Briatico-Vangosa, F.; Pavan, A. (Procedia Engineering, 2016)
In previous works, a finite element model of the shock absorbing characteristics of athletics tracks was developed, able to give sufficiently reliable predictions from laboratory tests performed on suitable material samples. The model proved to be effective in discriminating the effects of geometry (i.e. thickness) and material properties (essentially the elastic characteristics) on force reduction, thus allowing a first optimization of the tracks in view of their approval by the International Association of Athletics Federations (IAAF).